2016
DOI: 10.1002/jsfa.7831
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable intensification: a multifaceted, systemic approach to international development

Abstract: Sustainable intensification (SI) is a term increasingly used to describe a type of approach applied to international agricultural projects. Despite its widespread use, there is still little understanding or knowledge of the various facets of this composite paradigm. A review of the literature has led to the formalization of three principles that convey the current characterization of SI, comprising a whole system, participatory, agroecological approach. Specific examples of potential bottlenecks to the SI appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The study showed that gender differences existed in sustainable intensive farming practices such as minimum tillage, or adoption of livestock and poultry manure. Himmelstein et al (2016) argued that in the technology design of achieving sustainable intensification, some factors which are often overlooked in technology design or developing agricultural programs and sustainable agricultural practices, such as preferences, needs and women farmers' roles, should be taken into consideration [87]. Therefore, Snapp et al (2018) explicitly considered women's technology preference in the framework of sustainable intensification indicators.…”
Section: Changes In Socio-economic Factors Are the Main Factors Restrmentioning
confidence: 99%
“…The study showed that gender differences existed in sustainable intensive farming practices such as minimum tillage, or adoption of livestock and poultry manure. Himmelstein et al (2016) argued that in the technology design of achieving sustainable intensification, some factors which are often overlooked in technology design or developing agricultural programs and sustainable agricultural practices, such as preferences, needs and women farmers' roles, should be taken into consideration [87]. Therefore, Snapp et al (2018) explicitly considered women's technology preference in the framework of sustainable intensification indicators.…”
Section: Changes In Socio-economic Factors Are the Main Factors Restrmentioning
confidence: 99%
“…Thus, micro and meso level studies are important to inform planned agricultural interventions (see Sumner et al, 2017 for the importance of understanding gendered practices and perspectives in CA technology promotions). After a systematic review of sustainable intensification, Himmelstein et al (2016) advised that methodologies must depend upon adaptations of several development techniques for different types of communities. For this reason, the World Bank, in conjunction with TerrAfrica commissioned a study to build evidence on gender concerns in the context of projects and programmes focused on sustainable land management and climate change in Eastern Zambia.…”
Section: Introductionmentioning
confidence: 99%
“…Pretty et al mention 'legal status for land ownership' as a supportive public sector measure (2011, p. 20). Several authors assume that ownership and secure access to land could enable more smallholders (and specifically women) to participate in sustainable intensification practices (Himmelstein et al, 2016;Loos et al, 2014;Zimmerer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Mahon et al (2017) conclude that it should be a cause of concern that gender equity as an indicator was mentioned so few times in relation to SAI in their sample. Himmelstein et al (2016) write that if SAI approaches are to justify claims of being participatory and holistic, they need, among others, a stronger focus on gendered constraints and preferences. Loos et al (2014, p. 356) go even further by stating: 'Without specific regard for equitable distribution and individual empowerment (distributive and procedural justice) agricultural intensification cannot legitimately claim to be "sustainable"'.…”
Section: Introductionmentioning
confidence: 99%